Surface Investigation of Physella Acuta Snail Shell Particle Reinforced Aluminium Matrix Composites; Coatings; Vol. 12, iss. 6 - Pruncu C. I. Catalin Iulian; Vladesku A. Alina; Hynes N. R. J. Rajesh Jesudoss; Sankaranarayanan R. Ramakrishnan (2022, 2022)
Title screen